Secretion granules of transplantable pancreatic acinar carcinoma of rat. - Reddy, J K (1980)
Secretion granules of the rat transplantable pancreatic acinar carcinoma and of normal rat pancreas were isolated by differential centrifugation. Analysis of the granule content by sodium dodecyl sulphate/polyacrylamide-gel electrophoresis and isoelectric focusing procedures combined with specific enzyme assays indicated essential qualitative similarities between normal and neoplastic secretory proteins, suggesting retention of enzymic differentiation in this pancreatic acinar carcinoma. Accordingly, this epithelial tumor should serve as an important model for examination of regulatory mechanisms in cell differentiation and neoplasia.